IFN-α Neutralizing Antibodies Distinguish LADA From Early-onset Type 1 Diabetes - Amendolara, Rocco; D'Onofrio, Luca; Sessa, Rosario Luigi; Di Giulio, Stefano; Mignogna, Carmen; Coraggio, Lucia; Schirano, Roberto; Zampetti, Simona; Malandrucco, Ilaria; Pozzilli, Paolo; Giannini, Giuseppe; Maddaloni, Ernesto; et al. (The journal of clinical endocrinology and metabolism, 2025)
Autoantibodies against interferon-α (AAb-IFN-α) might be associated with the less aggressive autoimmunity in latent autoimmune diabetes in adults (LADA) compared to early-onset type 1 diabetes (T1D). To investigate the presence and clinical relevance of the positivity to AAb-IFN-α in people with LADA compared to T1D. Serum levels of AAb-IFN-α isoforms were measured using a cell-based approach in 41 subjects with LADA and 90 subjects with T1D. The primary and secondary outcomes were the difference between LADA and T1D in the proportion of participants testing positive for autoantibodies (AAb) against ≥2 and against 3 interferon-α (IFN-α) isoforms, respectively. The presence and levels of AAb-IFN-α were related to clinical and biochemical features of participants with LADA. Seven (17.1%) and 5 (12.2%) participants with LADA and 3 (3.3%) and 0 participants with T1D showed positivity for AAb against ≥2 and 3 IFN-α isoforms (P = .011 and P = .0025, respectively). Fasting blood glucose and hemoglobin A1c levels were numerically lower among people with LADA testing positive for AAb against ≥2 IFN-α isoforms than among those who were either negative or positive for AAb against 1 IFN-α isoform. Among LADA-positive individuals, levels of AAb-IFN-α2 isoform were inversely correlated with glutamic acid decarboxylase antibodies levels (rho = -0.513; P = .025). Autoimmunity against IFN-α is peculiar to autoimmune diabetes and appears to be distinctive to its slowly progressive forms. Understanding the underlying molecular mechanisms and clinical significance of this novel autoimmunity could lead to the development of new therapeutic strategies in autoimmune diseases, advancing personalized medicine.